Implementation of the Rational Emotive Behavior Therapy (REBT) Approach in Fostering Students' Learning Motivation - Rochanah Rochanah; Muhammad Silakhuddin (CV. Creative Tugu Pena, 2022)
Learning is a process that is pursued by each individual in order to achieve a better change and increase insight. It can be obtained through individual experiences with their interactions in the surrounding environment. This aricle analyzed the implementation of the Rational Emotive Behavior Therapy (REBT) Approach in fostering students' learning motivation. The method used a literature review, where the author conducts a literature review on the variables discussed, the results of which are presented in the form of document descriptions and arguments. While the review process involves several stages, first, giving coded the data, evaluated and looked for relevance, interpreted it in depth to conclude if the findings were relevant in answering valid questions. This study was entirely dependent on secondary data in the form of field details that have been published in various scientific publication journals. The results showed that the Rational Emotive Behavior Therapy (REBT) approach can increase students' learning motivation because this approach views humans as individuals who have a tendency to think irrationally and rationally. The Rational Emotive Behavior Therapy (REBT) approach eliminate emotional disorders that can damage the individual such as anxiety, feelings of hatred, feelings of fear, feelings of trouble, anger. Through the REBT approach, individuals with emotional disorders are treated to have high learning motivation so that the potential in students can develop optimally Keywords: Rational Emotive Behavior Theraphy, Learning Motivation, Emotional Disorders